DIGITAL MARKETING STRATEGIES FOR POSITIONING RELIGIOUS TOURISM DESTINATIONS: EVIDENCE FROM BOSNIA AND HERZEGOVINA - Njeguš, Angelina; Kosta, Ivan; Gajić, Jelena (The European Journal of Applied Economics, 2026)
This paper examines the role of digital marketing in positioning religious tourism destinations, focusing on Bosnia and Herzegovina (BiH). Using a mixed-method approach, the study integrates institutional and tourist perspectives to identify digital tools and governance strategies that improve destination visibility, visitor engagement, and competitiveness. Findings show a significant gap between the perceived potential of religious tourism and its limited operational framework, mainly due to institutional fragmentation and weak digital capacity. Social media, digital storytelling, and influencer collaborations stand out as key drivers of visitor decisions, loyalty, and destination image. The research introduces the Development–Cooperation–Dialogue framework, linking digital maturity and inter-institutional coordination as core factors of destination management in post-conflict, multi-faith societies. Policy recommendations emphasize the need for coordinated governance, digital innovation, and sustainable branding of sacred sites to boost Bosnia and Herzegovina’s visibility as a spiritual destination.
Keywords: religious tourism, digital storytelling, destination governance, Bosnia and Herzegovina, spiritual heritage.